Exercise capacity and haemodynamic response among 12, 327 individuals with cardio-metabolic risk factors undergoing treadmill exercise. (October 2017) - Chrysohoou, Christina; Skoumas, John; Georgiopoulos, Georgios; Liontou, Catherine; Vogiatzi, Georgia; Tsioufis, Konstantinos; Lerakis, Stamatios; Soulis, Dimitrios; Pitsavos, Christos; Tousoulis, Dimitris
Aims: Haemodynamic parameters during and after exercise test seem to have a role in predicting cardiovascular events. We sought to evaluate the potential different responses in exercise capacity, heart rate and blood pressure levels in relation to major cardiovascular disease risk factors, among individuals undergoing exercise tolerance testing. Methods and results: Consecutive individuals ( N = 12, 327), aged 55 ± 11.8 years, underwent exercise tolerance testing, using the Bruce protocol. Obese participants showed higher values of peak systolic and diastolic blood pressure ( p < 0.01), with no heart rate differences. Diabetic patients presented increased systolic blood pressure across the test ( p = 0.02) and decreased tolerance to exercise ( p = 0.05), but without differences in diastolic blood pressure or heart rate. Hypertensives showed exaggerated blood pressure, chronotropic response and decreased capacity to exercise ( p < 0.001 for all). Smokers had increased baseline systolic blood pressure, peak diastolic blood pressure and recovery heart rate and decreased tolerance to exercise ( p < 0.001 for all). For all high-risk subgroups, exercise testing was more often positive. Age-stratified analysis revealed different patterns: all four risk factors significantly decreased peak metabolic equivalent in subjects <50 years old ( p < 0.05 for all), while in participants between 50 and 69 years old, diabetes mellitus ( p = 0.03), hypertension ( p = 0.04) and smoking ( p = 0.01) predicted achieved metabolic equivalent. For patients of ≥ 70 years old, obesity ( p = 0.006) and hypertension ( p = 0.02) decreased peak metabolic equivalent and systolic blood pressure recovery. In subjects without pre-existing cardiovascular disease and negative exercise tolerance testing (7064 subjects, mean age: 52.4 ± 12.1 years, 62.9% males), age, obesity, hypertension and female gender inversely and independently predicted peak metabolic equivalent. Conclusions: High-risk individuals showed different haemodynamic responses when undergoing exercise tolerance testing, reflecting independent pathophysiological pathways.